Exploring Readiness of Teachers Toward English Remote Teaching - Ni Luh Ayu Gunawati Karuniasih (Journal of Educational Study, 2021)
Remote English teaching becomes a trend during the pandemic of Covid-19 outbreak. Schools in Indonesia are forced to conduct teaching and learning activity remotely during Work from Home (WFH) regulation. However, not all teachers were ready to teach virtually. This study aimed at investigating the teachers’ and students’ readiness toward remote English teaching. The subject were the English teachers at SMAN 1 Kubutambahan. An explanatory sequential mixed-method design was implemented in this research. The data were collected through an online survey and followed up with an interview. The data were collected through an online survey and analysed using Ideal Mean score analysis. The survey used a questionnaire which contain four dimensions, namely technology, innovation, people, and self-development to investigate the teachers’ and students’ readiness level.  The research finding showed that English teachers were categorized in the ready category, which means they were ready in conducting remote English teaching. The result of this research can be used as an evaluation for the teacher in order to improve their readiness level in the future.